A dual beam photonic wavelength refernce. (December 2021) - Hummon, Matthew; Bopp, Douglas; Kruse, Jesse; Yulaev, Alexander; Westly, Daron; Srinivasan, Kartik; Aksyuk, Vladimir; Kitching, John
Abstract: We present operation of a photonically integrated wavelength reference at 780 nm using a dual beam geometry. The dual beams are generated by a pair of extreme mode converting grating beam expanders that generate a pair of overlapped, counter-propagating beams inside the volume of a microfabricated vapor cell. We perform spectroscopy of rubidium and a characterize the stability of laser locked to a sub-Doppler transition at 780 nm. By stabilizing the laser to a known transition in an atomic vapor, this device can serve as a quantum wavelength reference. The dual beam geometry also enables investigation of two-photon absorption in a three-level ladder configuration in rubidium using excitation at 780 nm + 776 nm.